2020
DOI: 10.1002/jaba.721
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of modifications to the three‐step guided compliance procedure to enhance compliance among children with autism

Abstract: Three-step guided compliance (vocal prompt, vocal plus model prompt, vocal prompt plus physical guidance) is a commonly used procedure to increase compliance among children with intellectual disabilities. Previous research has suggested that under some conditions, slight modifications to the three-step procedure may enhance its effectiveness. These modifications include omitting the model prompt and decreasing the interprompt interval. In the current study, we evaluated another modification to the procedure: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Most research studies that have included demonstrations of treatment targeting noncompliance have been successful when they have included a DR component whereby compliance with a directive resulted in access to a preferred item, attention, and/or a break from work. For example, Wilder et al (2020) showed that the use of a three-step guided compliance procedure to treat noncompliance in two young boys with ASD was only successful when a DR component was included in the treatment package. However, DR alone is not always successful in treating noncompliance (e.g., Fischetti et al, 2012;Wilder et al, 2020), necessitating that other reinforcement-based approaches be considered for treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research studies that have included demonstrations of treatment targeting noncompliance have been successful when they have included a DR component whereby compliance with a directive resulted in access to a preferred item, attention, and/or a break from work. For example, Wilder et al (2020) showed that the use of a three-step guided compliance procedure to treat noncompliance in two young boys with ASD was only successful when a DR component was included in the treatment package. However, DR alone is not always successful in treating noncompliance (e.g., Fischetti et al, 2012;Wilder et al, 2020), necessitating that other reinforcement-based approaches be considered for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wilder et al. (2020) showed that the use of a three‐step guided compliance procedure to treat noncompliance in two young boys with ASD was only successful when a DR component was included in the treatment package. However, DR alone is not always successful in treating noncompliance (e.g., Fischetti et al., 2012; Wilder et al., 2020), necessitating that other reinforcement‐based approaches be considered for treatment.…”
Section: Introductionmentioning
confidence: 99%